Pathological studies and ORF 103 gene based molecular characterization of sheep pox virus from outbreaks in Maharashtra, India - VITTHAL, DHAYGUDE; BHUPESH, KAMDI; SHRUTI, BHOSALE; DIVYA, SABHARWAL; TEJASHRI, KULKARNI; BARATE, ABHIJIT (The Indian Journal of Animal Sciences, 2022)
Sheep and goat pox are endemic in India and causes considerable losses to the animal husbandry sector every year. There are multiple reports of this disease from different states of India; however, information on the occurrence of this disease in Maharashtra state is very scanty. In this context, the present investigation reports the outbreaks of sheep pox in Satara and Solapur districts of Maharashtra state, India, from August 2019 to February 2020 based on clinical signs, gross and histopathological lesions, and molecular detection. Additionally, the ORF 103 gene sequence analysis from field samples revealed 100 to 99% identity with SPPV from Egypt, China, Pune, Ahmedabad, and Makhdoom. In phylogeny, sequences of the present study grouped into SPPVs clade. The finding of this study adds to the knowledge of the epidemiology of sheep pox in Maharashtra state and may help in planning effective prevention and control strategies.